¿Qué hacer con los influencers? - Sosa Huapaya, Alex (2021)
In this article, the author develops the regulation related to advertising by influencers. In this sense, he concludes that said advertising is nothing more than a new way of doing testimonial advertising and that the possibility of dealing with concealed advertising is quite minor.